"(Review A) The Niqab: A Cross-Religious COVID-19 Safety Measure in Madina Zongo" - Anonymous (CERES / KHK Bochum, 2021)
This is the first review of the preprinted article "The Niqab: A Cross-Religious COVID-19 Safety Measure in Madina Zongo." The review will be taken offline once the final article has appeared. The reviewed article can be found under the following link: (PREPRINT) The Niqab: A Cross-Religious COVID-19 Safety Measure in Madina Zongo | Entangled Religions (rub.de)